Diagnostic utility of cytospin, cell block and immunocytochemistry in pleural effusion cytology - Miachieo, Nounechutuo; Kumar, Madhu; Sagar, Mala; Maurya, Malti Kumari; Kumar, Santosh; Kushwaha, R. A. S.; Goel, Madhu Mati (International Journal of Research in Medical Sciences, 2020)
Background: With the introduction of cytospin, the sensitivity of diagnosing malignancies has increased mainly due to the increase in cellular yield. Cell block also gives the advantage of ancillary testing and allows for retrospective studies. Immunocytochemical markers are used to differentiate and subtype various malignancies in body effusions. Aim of the study was to compare the morphological features of both technique and to assess the diagnostic utility of cell block methods in the cytodiagnosis of pleural effusions. Methods: This was a Prospective observational comparative study of two cytopreparatory techniques. All samples were examined and processed by cytospin and cell block techniques. Continuous data were expressed as Mean±SD (standard deviation) while categorical data were expressed in number, percentage and compared by chi-square (χ2) test. Results: The final diagnosis of both cytospin (147 cases) and cell block (150 cases) techniques was divided into four broad categories: Inadequate, Benign, Suspicious and Malignant. The significant diagnostic cytospin (AUC=0.857, p<0.001) in discriminating positive and negative malignant cases with 75.00% sensitivity (95% CI=53.3-90.2) and 100.00% specificity (95% CI=86.7-100.0) and with 100.0% positive predictive value and 81.2% negative predictive value. In contrast, cell block also showed significant diagnostic but with higher accuracy (AUC=1.000, p<0.001) and sensitivity 100.00% (95% CI=86.7-100.0) and specificity 100.00% (95% CI=86.7-100.0) and 100.0% positive predictive value and 100.0% negative predictive value than cytospin technique. Conclusions: Cell block as a technique should be used in routine practice as it not only increases the diagnostic yield but ancillary test can also be done.